Comparative Analysis of Factory Parts Supplier Performance Using the Vendor Performance Rating and Analytic Hierarchy Process Methods (Case Study of PT Pupuk Iskandar Muda) - Deny Novrizal; Edy Fradinata; Irwansyah; Yuwaldi Away; Iskandar Hasanuddin (International Journal Labs, 2026)
The availability of spare parts is the main factor that must be considered in the maintenance process so that maintenance can be carried out as planned. The availability of spare parts really depends on the procurement process which involves many parties including suppliers who are an important part of supply chain management in a company. Supplier assessment or evaluation in several previous studies was studied using several methods, including the Vendor Performance Rating (